Microbiologist’s Perspective on Innovative Triple-Action Antifungal Topicals: A New Frontier - I. E. Kasamba (Research Perspectives of Microbiology and Biotechnology Vol. 1, 2024)
This study investigated the effectiveness of triple-action antifungals containing azoles, gentamicin, and corticosteroids for superficial mycoses treatment. The antifungal association on the one hand with antibacterials will reduce the composition of the colonizing microbiota and promote fungal growth and improve fungal pathogenicity indirectly. The study identified 34 different antifungals in 588 pharmacies, with 47.05% being triple-action. While these combinations were expected to have excellent antifungal activity and prevent resistance, concerns arise regarding their impact on microbiota and potential for promoting fungal growth and pathogenicity. We suggest prioritizing antifungals without antibiotic and anti-inflammatory combinations to reduce recurrence rates.